The Role of Training and Mentoring in The Success of Small and Medium Community Enterprises in Accessing Credit - Yanti, Dewi Eka; Musmuliadi, Musmuliadi; Sabran, Sabran (Indonesian Journal of Business and Entrepreneurship Research, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an essential role in Indonesia’s economic development, including in Kutai Kartanegara Regency (Kukar). MSMEs contribute around 60% to the national Gross Domestic Product (GDP) and absorb more than 90% of the workforce. Although the number of MSMEs in Kukar continues to grow, many business actors still face challenges in accessing formal financial services. These difficulties are mainly caused by limited financial literacy, weak financial management skills, and challenges in meeting administrative requirements set by financial institutions. As a result, limited access to credit often restricts business expansion and sustainability for many MSMEs in the region. This study aims to examine the role of training and mentoring programs in improving MSME capacity to access formal credit in Kutai Kartanegara. The research uses a qualitative approach, with data collected through in-depth interviews involving MSME entrepreneurs, training facilitators, academics, and representatives of financial institutions. The findings show that training programs help improve financial literacy and managerial skills, particularly in financial planning, bookkeeping, and understanding credit requirements. Meanwhile, mentoring provides continuous technical assistance and moral support, enabling entrepreneurs to better understand credit application procedures and build trust with financial institutions. The combination of training and mentoring creates a sustainable empowerment process that increases business confidence and improves financial inclusion. MSME participants who obtained additional capital experienced revenue increases of approximately 20–30%, indicating that these programs contribute to business growth and local economic development in Kutai Kartanegara.